REFORMULATION OF ISLAMIC LAW STUDY METHODOLOGY (THEME STUDY AND STUDY METHODOLOGY IN JOURNAL ARTICLES IN MORAREF) - Harun, Muhamad; Fauziah, Fauziah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
In general, the study themes above are a grouping of religious studies that have been carried out so far. However, by not limiting it to aspects of current scientific developments, the possibility of combining analysis between one theme and another is possible. Because of this, it can also happen that the theme of religious studies depends on which aspect it is viewed from. Comprehensively, there are basically two paradigms that are often used in connection with religious studies, namely; logical and positivistic.